A new two-pored Amphisbaena Linnaeus from the endangered Brazilian Cerrado biome (Squamata: Amphisbaenidae) - Pinna, Pedro H.; Mendonça, André F.; Bocchiglieri, Adriana; Fernandes, Daniel S. (Zootaxa, 2010)
Amphisbaena carli sp. nov. is described from a Cerrado region in the southwestern of the state of Bahia, Brazil. The new species is diagnosable by having: small and separated nasal scales; two pre-cloacal pores separated from each other; 221–242 body annuli; 10–13 caudal annuli; 21–23 dorsal and 21–23 ventral segments to a midbody annulus; and tail without visible autotomic constriction. A proposition of standardization of head scalation nomenclature for amphisbaenids and comments on the current status of the genus Amphisbaena are also provided.